2020
DOI: 10.1021/acs.chemmater.0c02701
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Dramatically Improved Ammonia Synthesis Catalysts through Hierarchical High-Throughput Catalyst Screening of the Fe(211) Surface

Abstract: In order to improve efficiency of ammonia synthesis using the Haber−Bosch (HB) process with Fe-based catalysts, we employed quantum mechanics (QM)-based hierarchical high-throughput catalyst screening (HHTCS) of 49 possible metal dopants. Here, we consider the Fe( 211) surface (one of the two most active iron catalyst facets) to identify dopants that dramatically increase the turnover frequency (TOF) for HB synthesis. We found that under HB conditions, this surface reconstructs to form the Fe(211)R missing-row… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 44 publications
0
14
0
Order By: Relevance
“…This could help distinguish the two surfaces. For Co-doping of the bcc-(211)R surface, we found that the population of H on the surface in the resting states decreases appreciably, 14 for example, at 673 K and P(H 2 ) = 5 atm, P(N 2 ) = 5 atm, and P(NH 3 ) = 1 atm, 30% of sites are occupied with H for undoped and 19% for Co-doped: this change may be experimentally observable.…”
Section: T H I S C O N T E N T Imentioning
confidence: 83%
See 3 more Smart Citations
“…This could help distinguish the two surfaces. For Co-doping of the bcc-(211)R surface, we found that the population of H on the surface in the resting states decreases appreciably, 14 for example, at 673 K and P(H 2 ) = 5 atm, P(N 2 ) = 5 atm, and P(NH 3 ) = 1 atm, 30% of sites are occupied with H for undoped and 19% for Co-doped: this change may be experimentally observable.…”
Section: T H I S C O N T E N T Imentioning
confidence: 83%
“…Incorporating the reaction mechanisms into a kinetic Monte Carlo (kMC) model allowed us to predict Turnover-Frequency (TOF), in good agreement with single crystal experiments . In order to discover alloying elements to improve rates sufficiently to allow less severe reaction conditions (temperature and pressure) we have developed a hierarchical high-throughput catalyst screening methods that identified multiple doping strategies for improving HB. Thus, we found that doping Rh prefers the surface, whereas Si and Ni prefer the second layer, so that moderate levels of doping can achieve dramatic enhancements in catalytic rates on Fe-bcc(111). In addition, Co was found to prefer the subsurface for Fe-bcc(211)­R, leading also to improved rates .…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…Then, based on the derived reaction network, we developed a hierarchical high-throughput catalyst screening (HHTCS) approach to enable very rapid predictions to identify promising dopants that would dramatically improve reaction rates. , For Fe-bcc(111), screening 34 transition metal elements and 18 nontransition metal elements, we identified several candidates (Rh, Pt, Pd, Cu, Ni, Co, and Si) that could increase the overall reaction rates by factors of 4 to ∼40. Here we found that the best case is subsurface Si that would be 42 times faster at HB conditions, allowing a substantial reduction in the extreme HB industrial conditions (500 °C, 200 atm) to much milder conditions of either 500 °C at 20 atm or 400 °C at 60 atm while maintaining the same NH 3 production rates as HB on pure Fe-bcc(111) …”
Section: Introductionmentioning
confidence: 99%